A role for the macaque anterior cingulate gyrus in social valuation. - Rudebeck, P; Buckley, M; Walton, M; Rushworth, M (2006)
Complex human social interaction is disrupted when the frontal lobe is damaged in disease, and in extreme cases patients are described as having acquired sociopathy. We compared, in macaques, the effects of lesions in subdivisions of the anterior cingulate and the orbitofrontal cortices believed to be anatomically homologous to those damaged in such patients. We show that the anterior cingulate gyrus in male macaques is critical for normal patterns of social interest in other individual male or female macaques. Conversely, the orbitofrontal cortex lesion had a marked effect only on responses to mildly fear-inducing stimuli. These results suggest that damage to the anterior cingulate gyrus may be the cause of changes in social interaction seen after frontal lobe damage.